Ballooned neurons in semi-recent severe traumatic brain injury - Michaud, Jean; Plu, Isabelle; Parai, Jacqueline; Bourgault, André; Tanguay, Caroline; Seilhean, Danielle; Woulfe, John (Université d'Ottawa | University of Ottawa, 2023)
Abstract Traumatic brain injury (TBI) is now recognized as an insult triggering a dynamic process of degeneration and regeneration potentially evolving for years with chronic traumatic encephalopathy (CTE) as one major complication. Neurons are at the center of the clinical manifestations, both in the acute and chronic phases. Yet, in the acute phase, conventional neuropathology detects abnormalities predominantly in the axons, if one excludes contusions and hypoxic ischemic changes. We report the finding of ballooned neurons, predominantly in the anterior cingulum, in three patients who sustained severe TBI and remained comatose until death, 2 ½ weeks to 2 ½ months after the traumatic impact. All three cases showed severe changes of traumatic diffuse axonal injury in line with acceleration/deceleration forces. The immunohistochemical profile of the ballooned neurons was like that described in neurodegenerative disorders like tauopathies which were used as controls. The presence of αB-crystallin positive ballooned neurons in the brain of patients who sustained severe craniocerebral trauma and remained comatose thereafter has never been reported. We postulate that the co-occurrence of diffuse axonal injury in the cerebral white matter and ballooned neurons in the cortex is mechanistically reminiscent of the phenomenon of chromatolysis. Experimental trauma models with neuronal chromatolytic features emphasized the presence of proximal axonal defects. In our three cases, proximal swellings were documented in the cortex and subcortical white matter. This limited retrospective report should trigger further studies in order to better establish, in recent/semi-recent TBI, the frequency of this neuronal finding and its relationship with the proximal axonal defects.